CLINICAL-LABORATORY DIAGNOSIS AND PROGNOSTIC SIGNIFICANCE OF DYSLIPIDEMIA AND INFLAMMATION MEDIATORS IN METABOLIC PHENOTYPES OF OSTEOARTHRITIS: A META-ANALYTIC SYNTHESIS - Kurbonova Zumrad Chutbayevna; Saidrasulova Gulizebo Baxtiyorovna; Nuriddinova Shahlo Fazliddinovna (INTEGRATION OF EDUCATION AND SCIENCE: GLOBAL CHALLENGES AND SOLUTIONS, 2026)
Osteoarthritis (OA) is a paradigmatic degenerative joint disease, with metabolic phenotypes characterized by dyslipidemia—manifested as hypertriglyceridemia, accumulation of oxidized low-density lipoprotein (oxLDL), and reduced high-density lipoprotein (HDL)—interacting with inflammatory mediators (interleukin-6 [IL-6], tumor necrosis factor-alpha [TNF-α], C-reactive protein [CRP]). These interactions contribute to chondrocyte senescence, synovial effusion, and osteophyte formation via lipotoxic and inflammasome-mediated pathways. This synthesis underscores the growing burden of metabolic OA (projected 1 billion cases by 2050) and metabolic comorbidities (MetS prevalence 40–60%), advocating for lipid-modulating and anti-inflammatory interventions. Future metabolomic studies are warranted to refine causal inference and inform biomarker-guided therapeutic strategies.